Evaluation of a mobile C‐arm cone‐beam CT in interstitial high‐dose‐rate prostate brachytherapy treatment planning. Issue 2 (3rd April 2019) - Djukelic, Mario; Waterhouse, David; Toh, Ryan; Tan, Hendrick; Rowshanfarzad, Pejman; Joseph, David; Ebert, Martin A.
Abstract: Introduction: The aim of this study was to evaluate the suitability of using cone‐beam computed tomography (CBCT) obtained with a mobile C‐arm X‐ray fluoroscopy unit as a single modality for planning of high‐dose‐rate (HDR) prostate brachytherapy treatments. Methods: The feasibility of using CBCT images obtained using a Siemens Arcadis Orbic 3D mobile C‐arm was evaluated. A retrospective clinical study was undertaken of six participants undergoing HDR prostate brachytherapy. Plans generated using images from a Toshiba Aquilion One LB CT were compared with those generated using CBCT images. After rigid spatial registration, the plans were compared based on various parameters such as dose‐volume histograms, overlap quantities and metrics, and dose constraints. Results: Provided they were within the limited field of view, the brachytherapy catheters and fiducial markers were clearly visible in the CBCT images and thus, localisable and identifiable in the treatment planning process. The Siemens CBCT underestimated CT numbers leading to poorer tissue contrast which exacerbated the difficulties in delineation of the target tumour and the surrounding organs at risk. Between CT‐ and CBCT‐based plans, the mean difference of CTV‐ D 90 was 1.58 Gy, CTV‐ V 100 was 12.13%, rectum‐ V 80 was 0.06% and urethra‐ V 120 was −0.70%. Conclusion: It was not feasible to solely utilise the Siemens Arcadis Orbic 3D for HDR prostate brachytherapy treatment planning due to suboptimal organ delineation. However, the methods in this study could be used to evaluate other mobile CBCT imaging devices for feasibility in HDR brachytherapy treatment planning since the results indicated that it may not be necessary to have standard quality CT images for treatment planning. Abstract : Cone‐beam computed tomography (CBCT) scanners are becoming more available in surgical theatres and are commonly used for image guidance in radiotherapy, angiography and orthopaedics. This study describes an assessment of a mobile C‐arm CBCT unit (Siemens Arcadis Orbic 3D) for generating CT images for high‐dose‐rate prostate brachytherapy treatment planning. Following generic image quality assessments, an ethics approved retrospective clinical study was conducted to compare qualitative and quantitative differences of treatment plans created based on the Siemens CBCT images and CT images generated from the scanner routinely used (Toshiba Aquilion One LB).